The Democratic Potential of Parental Dissent: Keeping Public Schools Public, Legitimate, and Educational. Issue 3 (18th August 2020) - Stitzlein, Sarah M.
Abstract: In this essay, Sarah Stitzlein describes the democratic potential of parents choosing to opt out of school testing, explaining how they ought to engage in political dissent to best fulfill their responsibilities as citizens and to practice democracy on behalf of children and schools. Parents' decisions to opt out are often based on rights claims about their oversight as parents; moral claims regarding the potential undue pressure testing places on children and the misuse of students' scores; political and economic concerns with the role of corporations in testing; and educational claims about the validity of scores, the narrowing of curriculum, and the deprofessionalization of teachers who feel they must teach to the test. By building publics around these rationales and shared concerns, parents may increase the political legitimacy of public schools and create public schools that are more deeply public; in some cases, they may also provide an educational model of democratic life for budding citizens in schools to observe and learn from.